In his book 'Likelihood based inference in cointegrated Var', in order to get the expression for the Granger's representation theorem,, Johansen claims that:


$$\beta \bot(\alpha' \bot \beta \bot )^{-1} \alpha' \bot + \alpha (\beta' \alpha)^{-1} \beta' = I $$


$\alpha$ is NxR $\text{rank}(\alpha) =R$

$\beta$ is NxR $\text{rank}(\beta) =R$

$\beta \bot $ is NxN-R $\text{rank}(\beta \bot) =N-R$

$\alpha \bot $ is NxN-R $\text{rank}(\alpha \bot) =N-R$

$\alpha' \alpha \bot =0$

$\beta' \beta \bot =0$

I am not able to prove (1). Can you help me, please?


1 Answer 1


For ease of typing, let $$\eqalign{ A &= \alpha,\quad B=\beta,\quad X = \alpha\!\perp,\quad Y=\beta\!\perp \\ A^TX &= 0 \quad\implies X^TA = 0 \\ B^TY &= 0 \quad\implies Y^TB = 0 \\ }$$ Now consider the matrix $$\eqalign{ M &= Y(X^TY)^{-1}X^T + A(B^TA)^{-1}B^T \\ }$$ Straightforward calculations yield. $$\eqalign{ B^TM &= B^T \\ X^TM &= X^T \\ MA &= A \\ MY &= Y \\ M^2 &= M \\ }$$ The only idempotent $M$ which acts as an identity for all of those linearly independent row/column vectors -- recall that $(A,B,X,Y)$ are full rank -- is the identity matrix.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.